2022
DOI: 10.3847/1538-3881/aca1af
|View full text |Cite
|
Sign up to set email alerts
|

Deep Orbital Search for Additional Planets in the HR 8799 System

Abstract: The HR 8799 system hosts four massive planets orbiting 15 and 80 au. Studies of the system's orbital stability and its outer debris disk open the possibility of additional planets, both interior to and exterior to the known system. Reaching a sufficient sensitivity to search for interior planets is very challenging due to the combination of bright quasi-static speckle noise close to the stellar diffraction core and relatively fast orbital motion. In this work, we present a deep L-band imaging campaign using NI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Directly modeling point sources in images is one of the key features of Octofitter. This is accomplished with the same approach described in Ruffio et al (2018) and applied in Mawet et al (2019), Llop-Sayson et al (2021), and Thompson et al (2023. In the case where a planet is robustly detected in each image and the uncertainties are well-approximated by Gaussian uncertainties, it is mathematically equivalent to extracting the relative astrometry and photometry and then modeling those measurements.…”
Section: Imagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Directly modeling point sources in images is one of the key features of Octofitter. This is accomplished with the same approach described in Ruffio et al (2018) and applied in Mawet et al (2019), Llop-Sayson et al (2021), and Thompson et al (2023. In the case where a planet is robustly detected in each image and the uncertainties are well-approximated by Gaussian uncertainties, it is mathematically equivalent to extracting the relative astrometry and photometry and then modeling those measurements.…”
Section: Imagesmentioning
confidence: 99%
“…These include a search for planets around Sirius B (Skemer & Close 2011), K-Stacker (Nowak et al 2018;Le Coroller et al 2020), PACOME (J. Dallant et al 2023, submitted), the search for planets around ε Eri (Mawet et al 2019;Llop-Sayson et al 2021), and the search for additional HR 8799 planets by Thompson et al (2023). These have now led to promising evidence for α Cen AB b (Le Coroller et al 2022) and HR 8799 f (Thompson et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dots show the experimental data for 3 × 3, 7 × 7, and 15 × 15 pixels, in pink, blue, and red, respectively. (6)] by considering all the potential correlations within the sliding window. In this case, the correction factors are K s ð3 2 ; 1Þ ¼ 0.7073 and K s ð7 2 ; 3Þ ¼ 0.8198, respectively.…”
Section: Experimental Validation Of Proposed Modelmentioning
confidence: 99%
“…They generally assume distributions that are uniform (for the eccentricity, argument of periastron, and period of ascending nodes), log-uniform (semimajor axis) and sine (inclination). It is also common practice to narrow down the parameter space with physically motivated priors, such as stability constraints, coplanarity and stellar rotation rates (e.g., Pearce et al 2015;Wang et al 2018;Wang et al 2020;Thompson et al 2023;Yimiao Zhang et al 2023). However, for orbits where less than 40% of the orbital arc is covered, which is the majority of directly imaged companions, this standard method of model-based priors (which herein we will refer to as "uniform" priors, as is done by O'Neil et al 2019) has been shown to introduce biases in the resulting posterior distributions, generating inaccurate parameters and confidence intervals (Lucy 2014;Martinez et al 2017).…”
Section: Introductionmentioning
confidence: 99%